Isolated hypoxic pelvic perfusion combined with electroporation is a valid alternative to traditional therapies for anal squamous cell carcinoma: a case study - Aigner, Karl R.; Aigner, Kornelia; Hendrikx, Marc J. H.; Bekrentchir, Abderrahmane; Aust, Hansjörg (Frontiers in Oncology, 2025)
IntroductionWe report a series of four patients with HPV-positive squamous cell carcinoma of the anus: two with non-previously treated grade G3 malignancies, and two with relapsing G2 tumors in progression after chemoradiation.MethodChemo-naive patients were treated with isolated hypoxic pelvic perfusion, whereas the two patients with local recurrences both received isolated hypoxic pelvic perfusion and concomitant reversible electroporation.ResultsThe two patients without prior therapy showed a complete clinical and pathological response, one after two and one after three therapies. In the two patients with local recurrences, a clinico-pathological complete remission occurred after two isolated perfusions with electroporation. The two techniques combined produce highly effective drug exposure that leads to complete remission; subsequent blood purification by chemofiltration avoids toxic side effects and cumulative toxicity. The therapies caused no side effects affecting quality of life. No recurrences occurred in the observation period of 48, 27, 10 and 8 months.ConclusionIsolated hypoxic pelvic perfusion with electroporation is an effective, low-toxicity valid alternative to traditional therapies for the treatment of anal squamous cell carcinoma.